Pelatihan Pembuatan Kreasi Masker Bagi Anak Panti Asuhan Putri Aisyiyah Yogyakarta - Teti Anggita Safitri; Rigel Nurul Fathah (Jurnal Ilmiah Pangabdhi, 2021)
The community partnership program was carried out with partners, namely the Children of the Putri Aisyiyah Orphanage, Yogyakarta. This service aims to assist partners in solving the problems they have, namely: (1) There is no education regarding the benefits of using masks during a pandemic; (2) There is no training to develop creativity in the orphanage children; (3) There has been no training related to making patterned masks. The solution offered is training in making patterned masks for the Children of the Putri Aisyiyah Orphanage in Yogyakarta so that it was hoped that it can educate children about the benefits of using masks during the Covid-19 pandemic and foster creativity in creating masks with the decoupage technique. The method of the community partnership program is training in making patterned masks in the form of lectures, discussions and practice of making patterned mask creations for the children of the Putri Aisyiyah Orphanage in Yogyakarta. This community partnership program was aimed at children of members of the Putri Aisyiyah orphanage with various ages.